БИР ТУРКУМ ДОИРАСИДАГИ ОМОНИМ СЎЗЛАР ҚУРШОВИНИ ЛИНГВИСТИК МОДЕЛЛАШТИРИШ МАСАЛАСИ - Гулямова, Ш.К. (SCIENCE and SOCIETY, 2021)
This article presents the results of a study on the topic of linguistic modelling of the environment of homonymous words in the framework of the series and highlights its practical significance.
Keywords: semantic analyzer; corpus; linguistic model; modelling; semantic and morphological filter; homonym; right connective; left connective